Umbrales de sentido musical: reflexiones en torno al ruido - Macotela Aldrete, Jonathan Sibraim (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
In this work, I present the idea of noise (not to be mistaken with the genre) as a type of sound product that has as its main feature the transgression of common values related to music, such as rhythm, pitch, timbre, and structure. Then I argue that the problem between music and noise can be pictured as one related to a wrong interpretation of the concept of sense (Sinn) with Husserl's doctrine of intentionality in the background. While music acquires sense as meaning achieved in the correlation between signs, values, and codes; noise attains its sense through aesthetical listening. After this, I propose a description of a piece of noise to attest to the fullness and richness of sense ingrained in it. Finally, starting from the distinction between the aesthetic object and the natural object made by Mikel Dufrenne, I speculate about noise as a sort of embodiment of Nature amid of Culture.

En este trabajo propongo al ruido como un tipo de producción sonora que tiene como característica principal la de contravenir valores comunes de lo musical tales como ritmo, altura, timbre y estructura. Tras esta identificación sitúo la cuestión como una problemática relativa al sentido (Sinn) en el contexto de la doctrina de la intencionalidad husserliana: mientras la música requiere una escucha de significaciones para tener sentido, el ruido requiere de una escucha estética. Tras estas definiciones, llevo a cabo una descripción de una obra que cumple las características del ruido, y con ello subrayo la riqueza de sentido fuera de las significaciones musicales. Finalmente, a partir de la distinción entre objeto estético y objeto natural hecha por Mikel Dufrenne, especulo sobre la posibilidad de considerar al ruido como un tipo de manifestación de la Naturaleza en medio de la Cultura.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2023-0954; Música; Significación; Fenomenología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16672